Innovative marking method using novel endoscopic clip equipped with fluorescent resin to locate gastric cancer. Issue 2 (27th July 2020) - Namikawa, Tsutomu; Hashiba, Motoi; Kitagawa, Hiroyuki; Mizuta, Hiroshi; Uchida, Kazushige; Sato, Takayuki; Kobayashi, Michiya; Hanazaki, Kazuhiro
Abstract: An asymptomatic 76‐year‐old man presented to our department for the treatment of gastric cancer. Esophagogastroduodenoscopy revealed a superficial elevated lesion with an irregular central depression in the lower third of the stomach; this was confirmed to be adenocarcinoma by biopsy, while abdominal contrast‐enhanced CT revealed no abnormal lesions. Based on the patient's clinical diagnosis of early gastric cancer, we planned laparoscopic gastrectomy with preoperative placement of four endoscopic marking clips equipped with indocyanine green‐conjugated resin to determine the resection margin. During surgery, a dedicated laparoscopic system was used to detect indocyanine green fluorescence emitted by the clips and determine their precise position. The clips helped to identify an accurate resection line for the stomach, enabling accurate laparoscopic distal gastrectomy with regional lymphadenectomy. We successfully demonstrated the usefulness of clips with fluorescent resin for detecting gastric cancer in patients. We report the first case using the clips to accurately locate a site of interest.